Mass-Like Fat at the Medial Midfoot: A Common Pseudolesion - Strickland, Colin D.; Patten, Luke W.; Durst, Michael J.; Merkle, Alexander N. (Indian Journal of Radiology and Imaging, 2021)
Background Fatty masses are common and may be encountered in the foot and ankle. In some cases, normal subcutaneous fat may be mistaken for a discrete mass.Aims The aim of this study was to evaluate the common finding of prominent subcutaneous fat at the medial midfoot resembling a lipoma and to determine the prevalence of this pseudolesion by applying a series of potential size cutoff criteria.Materials and Methods Three musculoskeletal radiologists retrospectively evaluated 91 sequentially performed magnetic resonance imaging examinations of the ankle to measure fat resembling a discrete lipoma at the medial midfoot. Each blinded reader measured the largest area of continuous subcutaneous fat in orthogonal axial, coronal craniocaudal, and coronal transverse dimensions. Patient age, sex, and study indications were also recorded. Statistical analysis was performed with R and SAS 9.4 softwareResults A discrete fatty pseudolesion as defined by measuring at least 1 cm in all planes by measurements of at least two of three readers was present in 87% of cases (79 of 91). When a size criterion of 1.5 cm was used, a pseudolesion was documented in 14% of cases (13 of 91). There was a significant correlation between larger pseudolesion size and female sex in the axial plane; however, there was no correlation in the coronal craniocaudal and coronal transverse dimensions.Conclusions Subcutaneous fat at the medial midfoot often has a mass-like appearance that could be mistaken for a lipoma. It is important to recognize this pseudolesion variant and not to confuse the imaging appearance for a discrete mass.
Keywords: lipoma; midfoot; mass